Individual, sexual and temporal variation in the winter home range sizes of GPS-tagged Eurasian Curlews Numenius arquata. Issue 1 (3rd April 2022) - Mander, Lucas; Nicholson, Ian; Green, Ros M.W.; Dodd, Steve G.; Forster, Rodney M.; Burton, Niall H. K.
ABSTRACT: Capsule: Eurasian Curlews Numenius arquata were faithful to foraging and roosting areas on their coastal wintering grounds, including a habitat creation site. Home range sizes were greater at night than during the day, and showed high inter-individual variability which was not related to sex. Aims: To examine factors affecting variation in the winter home range size of the largest European wader species: the near-threatened Eurasian Curlew Numenius arquata . Methods: We examined individual, sexual and temporal (day/night, seasonal and annual) variation in the size of the home ranges of 18 GPS tagged Curlews captured at two sites on the Humber Estuary, UK. Results: Home ranges were small (mean ± SD = 555.5 ± 557.9 ha) and varied slightly in size through the non-breeding season (September–March). We found some annual differences in home range size, and there was some evidence that home range size was greater at night compared to daytime. There was strong inter-individual variation in home range size, which was not related to the species' sexual size dimorphism and thus potential differences in resource use. Conclusions: Our results highlight that wintering Curlews on the Humber Estuary maintain small home ranges which vary strongly between individuals. Knowledge of the home range size of wintering waders is vital to inform management responses to the potential impacts of environmental changes such as sea-level rise and improving the efficacy of compensatory habitats.